GROUNDNUT SHELL ASH AS PARTIAL REPLACEMENT OF CEMENT IN CONCRETE - Krishnan, C.Navaneetha; Nizar, N.Mohamed (IJRDO - Journal of Mechanical And Civil Engineering, 2016)
Concrete is always valuable product in construction industry. The concrete ingredients are cement, coarse aggregate, and water. Nowadays there is a scarcity of concrete materials, so we are in need to find out the alternative materials to concrete. In this situation we should utilize the larger amount of waste products which is available. For example plastic wastages, agriculture wastages, rise husk ash etc., This experimental investigation was performed to evaluate the strength of concrete, in which cement was replaced from 0% to 10% percentage with ground nut shell ash (GSA).Test were conducted on Fresh concrete testes for M20 concrete using IS method.